Pelatihan Penguatan Kelembagaan dan Tata Kelola Koperasi Modern Sektor Pangan di Pekanbaru Provinsi Riau - Wahyuningsih, Endang (LPPM Universitas Koperasi Indonesia, 2025)
Training on institutional strengthening and management of modern cooperatives in the food sector in Riau Province, Pekanbaru City was held for three days from 24 to 26 September 2024 with a total of 24 training hours organized by the Ministry of Cooperatives and MSMEs in collaboration with the Indonesian Cooperative University by providing material in the form of Cooperative Management, Cooperative Financial Management and Cooperative Business Digitalization. There were 30 training participants of the cooperative boards and supervisors. The training method used in this training is presentation of material, discussion and discussion of cooperative cases of training participants. The material provided regarding cooperative management consists of: understanding, organization and values ​​and principles of cooperatives as an identity as the basis for cooperative activities. Cooperative financial management material consists of concepts and their application in cooperatives in terms of capital, and how to assess cooperative financial performance. The cooperative digitalization material consists of concepts and applications that can be taken as examples to be applied to each participant's cooperative.